POTENSI KERAPATAN VEGETASI TERHADAP KONDISI AIR TANAH DESA LOSARI KECAMATAN RAWALO BANYUMAS (STUDI KASUS DAS SERAYU) - Hafidzah, Fida; Kartikasari, Lilik (JURNAL TEKNIK GEOLOGI : Jurnal Ilmu Pengetahuan dan Teknologi, 2025)
Losari Village is one of the villages located in Rawalo District, Banyumas Regency, Central Java which is included in the Serayu Watershed area. The location of Losari Village is in a lowland area with an altitude of around 50-100 meters and is included in the middle of the Serayu Watershed. Changes in land use due to urbanization and intensive agricultural activities in recent years have triggered various environmental problems that have an impact, especially on changes in the potential density of vegetation and water conditions. The need for monitoring of changes in structure and composition that are carried out periodically in order to prevent an increase in land and water use. The purpose of this paper is to determine the density of vegetation in Losari Village in 2022-2024 and the potential density of vegetation on groundwater conditions in Losari Village. Data collection methods use observation, documentation, and questionnaires. The data analysis technique used is quantitative descriptive and data retrieval of vegetation density from Lansat-8 satellite imagery and processed using the ArcGis application and checking the quality of groundwater in Losari Village, Rawalo District, Banyumas. The vegetation density of Losari Village in 2022-2024 shows that the increasing population and development of an area can affect the vegetation density in the area. Reduced vegetation density will affect the environment, especially groundwater conditions. The conclusion in the relationship between vegetation density and groundwater conditions shows a fairly significant pattern where areas with denser vegetation tend to have better groundwater reserves. Keyword: Losari Village, Vegetation Density, Groundwater.